2012
DOI: 10.3892/ol.2012.802
|View full text |Cite
|
Sign up to set email alerts
|

14-kDa Phosphohistidine phosphatase plays an important role in hepatocellular carcinoma cell proliferation

Abstract: Abstract. 14-kDa Phosphohistidine phosphatase (PHP14), the first histidine phosphatase protein identified in vertebrates, was recently revealed to play an essential role in lung cancer. The function of this gene in other tumors is unclear; however, in this study, we demonstrate that PHP14 is highly expressed in hepatocellular carcinoma (HCC) tissues and cell lines compared with adjacent non-cancerous human liver tissues and cells (P<0.05). We used lentivirus-mediated delivery of small interfering RNA (siRNA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The identities of the pHis proteins we identified suggest that pHis may play a role in mammalian cell signaling [32][33][34] . Indeed, a direct correlation of pHis protein levels with carcinogenesis has recently been reported 30,[35][36][37] . Interestingly, we identified 20 N-phosphate sites on proteins that were reported to be enriched by IAP by Hindupur et al from mTOR-driven hepatocellular carcinoma mouse tumors as potential LHPP substrates, including BCLAF1, which in our studies was found to contain pLys (K391) with a reasonable probability of localization of 79.6%.…”
Section: Discussionmentioning
confidence: 95%
“…The identities of the pHis proteins we identified suggest that pHis may play a role in mammalian cell signaling [32][33][34] . Indeed, a direct correlation of pHis protein levels with carcinogenesis has recently been reported 30,[35][36][37] . Interestingly, we identified 20 N-phosphate sites on proteins that were reported to be enriched by IAP by Hindupur et al from mTOR-driven hepatocellular carcinoma mouse tumors as potential LHPP substrates, including BCLAF1, which in our studies was found to contain pLys (K391) with a reasonable probability of localization of 79.6%.…”
Section: Discussionmentioning
confidence: 95%
“…[45] The intermediate conductance Ca 2 + -activated K + channel (SK4) [46] and transientr eceptor potentialc hannel 4 (TRPC4) have also been proposed as in vivo targets of PHPT1; [47] thus implicating the role of PHPT1 in vasculoproliferative diseases and insulin secretion. Severals tudies indicated that higherl evels of PHPT1 expression were associated with lung, [48,49] renal, [50] and liver [51] cancers. PHPT1 knockdown in these cancer cells inhibited cell proliferation, which supported the potential therapeutic values of PHPT1-specific inhibitors.…”
Section: Phpt1mentioning
confidence: 99%
“…The interesting possibility of NDPK acting as a protein kinase with PHPT1 as the balancing phosphoprotein phosphatase has been discussed in a review by Wieland et al ( 30 ). Furthermore, evidence for a possible role of PHPT1 in cytoskeletal reorganization ( 31,32 ) and in hepatocellular carcinoma cell proliferation ( 33 ) has been presented. In several of the experiments above, the possibilities to modulate the expression of the PHPT1 gene have been crucial.…”
Section: Introductionmentioning
confidence: 99%